2023
DOI: 10.53471/bahce.1085986
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition and Biodiesel Quality of Brassica nigra, Brassica napus and Sinapis arvensis Seeds

Abstract: The increasing world population and developing industrial areas increase the need for energy. This situation makes alternative and renewable energy sources and the efficient use of these sources more valuable. In this study, the seeds of Sinapis arvensis, Brassica nigra, and Brassica napus from Brassicaceae family grown in ecological conditions of Bayburt province of Turkey, to determine the usability potential of wild species in biodiesel production. Biodiesel quality characteristics and oil yield and fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lipid production and fatty acid compositions should be assessed to define the quality of oil crops. The oil content and fatty acid compositions of S. arvensis, B. nigra, B. napus, S. alba, and C. sativa make them valuable plants (Al-Shehbaz et al, 2006;Gıdık et al, 2023). Mandal et al, (2002) have reported that the total oil contents of B. nigra changed between 21.5% and 33.9% and the amount of erucic acid changed between 39.1%-47.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid production and fatty acid compositions should be assessed to define the quality of oil crops. The oil content and fatty acid compositions of S. arvensis, B. nigra, B. napus, S. alba, and C. sativa make them valuable plants (Al-Shehbaz et al, 2006;Gıdık et al, 2023). Mandal et al, (2002) have reported that the total oil contents of B. nigra changed between 21.5% and 33.9% and the amount of erucic acid changed between 39.1%-47.2%.…”
Section: Introductionmentioning
confidence: 99%